Correlation of sonographic features with prognostic factors in ductal carcinoma in situ of the breast: an exploratory study using ultrasound and shear wave elastography - Jianan Shi; Shiyun Yang; Qinghua Niu; Lei Zhao; Chao Jia; Lianfang Du; Fan Li; Yang Liu (BMC Medical Imaging)
Abstract Objective Ductal carcinoma in situ (DCIS) of the breast has a wide disease spectrum with risks of progression to invasive cancer linked to pathological factors. High-grade histology, large tumor volume, and comedonecrosis are adverse prognostic factors. This study explores the correlation between conventional ultrasound (Con-US) and shears wave elastography (SWE) features with DCIS prognostic factors and evaluates their predictive efficacy. Methods A retrospective analysis was conducted on clinical data, Con-US, and SWE imaging features of 83 DCIS patients who underwent surgical resection between June 2018 and December 2022. Binary logistic regression analysis was performed to explore the relationship between sonogram indices and pathological prognostic factors. Results The results revealed that microcalcification observed on Con-US was an independent risk factor for high-grade DCIS and comedonecrosis [odds ratio (OR): 5.316 and 4.512]. In SWE analysis, the Emax value was significantly different between the non-high-grade and high-grade DCIS groups(P = 0.006), with an Emax value greater than 75.03 kPa identified as an independent risk factor for high-grade DCIS [OR:1.022, the area under the curve (AUC): 0.682, 95% confidence interval (CI): 0.555–0.808]. Additionally, the Ecolor, Emax, Emean, and Emean SD values were statistically different between the groups with and without comedonecrosis (P = 0.049, 0.006, 0.012, 0.022), with an Emean value exceeding 30.45 kPa identified as an independent risk factor for comedonecrosis (OR:1.025, AUC:0.708, 95% CI:0.562–0.854). Furthermore, combining microcalcification on Con-US with specific SWE indicators demonstrated an improved predictive specificity for high-grade DCIS and comedonecrosis (0.902 and 0.889, respectively). No significant difference was found in other indexes on SWE. Conclusions The microcalcification signs on Con-US, Emax and Emean values on SWE analysis are associated with the high nuclear grade and comedonecrosis of DCIS, the combination of Con-US and SWE can improve the predictive specificity of DCIS-related prognostic factors.